Autonomy and Dependency in Two Successful UK Film and Television Companies: An Analysis of RED Production Company and Warp Films. Issue 1 (1st May 2016) - Spicer, Andrew; Presence, Steve
Abstract : This article analyses the production cultures of two film and television companies in the United Kingdom – RED Production and Warp Films – by discussing the companies' formation and identity, aims and ethos, internal structures and their networks of external relationships. The article argues that although managing directors and senior personnel exercise considerable power within the companies themselves, the companies depend on the extent to which they are able to engage with other industry agents, in particular the large-scale institutions that dominate the film and television industries. By situating analysis of these negotiated dependencies within shifting macroeconomic, historical and cultural contexts, the article argues that the increasing power of multinational conglomerates and the cultural convergence between film and high-end television drama marks a threshold moment for both companies which will alter their production cultures significantly.